2016
DOI: 10.1136/vr.103580
|View full text |Cite
|
Sign up to set email alerts
|

Axillary temperature measurement: a less stressful alternative for hospitalised cats?

Abstract: Rectal temperature measurement (RTM) can promote stress and defensive behaviour in hospitalised cats. The aim of this study was to assess if axillary temperature measurement (ATM) could be a reliable and less stressful alternative for these animals. In this prospective study, paired rectal and axillary temperatures were measured in 42 cats, either by a veterinarian or a student. To assess the impact of these procedures on the cat's stress state, their heart rate was checked and a cat stress score (CSS) was def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…The skin or body surface temperature is thought to be several degrees below RT ( 28 ). This difference ranged from −2.1°C to 3.6°C ( 8 ) in cats and from −1.3°C to 0.5°C in dogs ( 29 ). In children, the mean difference RT - surface temperature was only 0.29°C ( 30 ).…”
Section: Introductionmentioning
confidence: 99%
“…The skin or body surface temperature is thought to be several degrees below RT ( 28 ). This difference ranged from −2.1°C to 3.6°C ( 8 ) in cats and from −1.3°C to 0.5°C in dogs ( 29 ). In children, the mean difference RT - surface temperature was only 0.29°C ( 30 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the study by Girod and others (2016) documented a significant influence of gender and coat length on the rectal-axillary temperature gradient. Therefore, the reliability of these techniques may be heavily influenced by factors that are far from completely controlled in a clinical environment.…”
mentioning
confidence: 99%
“…However, a paper by Girod and others (2016), which is summarised on page 192 of this issue of Veterinary Record , investigates how reliable and stressful axillary thermometry was compared to rectal thermometry in hospitalised cats. The authors found a moderate correlation between the two techniques, but the difference between axillary and rectal temperatures documented in their study was highly variable, ranging from –2.1°C to 3.6°C.…”
mentioning
confidence: 99%
See 2 more Smart Citations